Testing a proactive model of successful aging among older adults in Costa Rica and Spain - Blanco-Molina, Mauricio (2021)
The purpose of this study is to examine successful aging among Spanish-speaking older adults in Costa Rica and in Spain using the proactive framework proposed by Kahana et al. (2014). More specifically, we hypothesized that older adults’ life satisfaction would be positively associated with the frequency and perceived level of social support, spirituality/having purpose in life, and the use of proactive physical, cognitive, and social self-care behaviors. Our results confirmed these hypotheses, not only for the overall group of participants, but also separately for older adults in Costa Rica and in Spain. The present study contributes to the literature of successful aging among older adults, by examining the protective factors associated with life satisfaction among Spanish speaking older adults in Costa Rica and in Spain. It identifies specific protective factors (spirituality/purpose in life, social support, and self-care) associated with the values and preferences held by participants in the study.